(untitled) (Medico Legal Update, 2020)
Background/Objectives: To find relationships among stress, self-differentiation, and adjustment to college life in the college students and verify the mediated effect of self-differentiation between stress and adjustment to the college life. Method/Statistical Analysis: Data were collected from 1,192 attending college students and analysed using SPSS Statistics 22. T-test and ANOVA were used to confirm the level of stress by the adjustment level to the college life, differences of self-differentiation, adjustment level to the college life by the levels of stress and self-differentiation. Findings: Even with the same level of stress, there were differences in the adjustment to the college life by degree of self-differentiation. The stress and self-differentiation of the college students were significant predictors for the adjustment to the college life by 15.8%, which showed higher level of the adjustment to the college life as the stress was lower and self-differentiation was higher, demonstrating partial mediated effect of self-differentiation between the stress and adjustment to the college life. Improvements/Applications: Based on these study results, controlling stress by enhancing self-differentiation is considered to be helpful for the adjustment to the college life.